The Potential Impacts of Hydraulic Fracturing on Agriculture - Ong, Beng (European Journal of Sustainable Development, 2014)
Hydraulic fracturing (or “fracking”) is a method of extracting oil and natural gas trapped in deep rock layers underground by pumping water, sand, and other chemicals/additives at high pressures into a well drilled vertically, and then horizontally into the rocks. Advocates of fracking in U.S. have skillfully positioned domestic natural gas as a sensible alternative energy to the country’s goals of reducing carbon emissions and dependence on foreign oil, while simultaneously creating jobs locally. Opponents to fracking, however, alleged that the process pollutes the air, contaminates the soil and water, particularly in farming/rural communities. Due to page limitson this paper, we discussed only the potential impacts of hydraulic fracturing on water, and consequently, agriculture. Any impact on agriculture extends beyond the perimeter of a farm or plot of rural land where fracking operations occur. Fruits, vegetables, dairy, and meats from an impacted farming region may be shipped to other parts of the country, or even internationally. Fracking challenges stakeholders to confront the trade-offs between economic development and public health/safety; thus multiple viewpoints and issues were raised. Keywords: Hydraulic Fracking; Environmental Sustainability; Water Contamination; Agriculture vs. Energy; Shale Gas.